Variety Study on Germination Power of Palm Seeds (Elaeis guineensis Jacq.) - Yabani Yabani; Retna Astuti Kuswardani; Agus Susanto; Saipul Sihotang (Universitas Labuhanbatu, 2024)
Seeds as planting material play an important role in agricultural development. The high demand for oil palm sprouts causes the long germination time to become an obstacle for consumers and seed producers. The aim of this research is to examine varieties on germination capacity of oil palm seeds. Research was conducted at the PPKS Seed Processing Unit on nine PPKS varieties (Simalungun, PPKS 540, Yangambi, PPKS 239, PPKS 718, Dumpy, Avros, Langkat, and PPKS 540 NG). The parameter observed was the germination power (DB) of the seeds. The treatment given in the germination process for all varieties is carried out to ensure that the environment is favorable for germination (according to the SOP). Observation results showed that PPKS 540 variety had the highest DB (84.9%), followed by Simalungun (81.46%), PPKS 540 NG (75.46%), Langkat (75.43%), Dumpy (73.41 %), PPKS 718 (72.29), Yangambi (68.81%), PPKS 239 (65.74%), and Avros (56.92%). This is thought to be due to the influence of internal factors, related to the conditions of the germinated seeds, both genetics and hormones, as well as external conditions which include optimal water, temperature and oxygen treatment during germination. The results show that the water content (KA) of the seeds in the soaking period (I) was 16-20%, and soaking (II) was 19-22%, all processed seeds were still at a safe level of water content for the process of breaking dormancy of oil palm seeds. The characteristics of parent tree of the seed variety are the cause of differences in seed germination